Challenges of Working From Home in Persistent Covid-19 Environment - P.M, Chinnaiah; P, Smt. Chythra (Universitas Prasetiya Mulya, 2021)
The IT sector is one of the important sectors that contribute to the growth of Indian economy. The Industry adopted many measures to achieve a higher level of performance and to sustain their higher market share; one of such measures is working from Home (WFH). The Covid-19 pandemic badly affected the world economy. Therefore, to sustain the work progress the IT firms across the globe have adopted WFH method. Though there are many studies conducted to identify the challenges of working from home in the early stage of the covid-19. But, there are scant studies those who made attempt to identify the challenges of working from home and changes in these challenges in the persistent covid-19 environment. In the present study it is found that, there are seven challenges remain same as in the early stage of pandemic and eight previously identified challenges have changed into moderate challenges.